Effects of Transformational Leadership on Follower's Organizational Citizenship Behavior : The Moderating Role of Culture - Choudhary, Neetu; Kumar, Rajender; Philip, P. J. (Prabandhan: Indian Journal of Management, 2016)
The present research aimed to explore the relationship between transformational leadership and organizational citizenship behavior across three different cultures, and also to test the moderating role of culture on the relationship between the above two stated variables. A sample comprised of 142 teaching professionals working in China, India, and Australia. The results showed that there was a significant relationship between transformational leadership and OCB in China and Australia, but partially in India. Besides, out of the five cultural dimensions, only individualism and uncertainty avoidance significantly varied across the samples from the three countries. There has been inconsistency in researchers' work about the relationship between OCB and transformational leadership in the public sector across the three countries. So, this study attempted to fill this lacuna by studying the relationship between transformational leadership and OCB.